Использование компьютерных учебно-деловых игр в условиях инновационного развития образовательных систем - Карауылбаев, С.К. (My University, 2016)
The article describes the experience of effective use of information technology in the education system - as one of important methodological problems of pedagogy in terms of innovative development of educational systems. Currently, the level reached a new level of information, training and use of computer gaming, the availability of content online educational institutions, a unified information environment of the university contribute to improving the quality of education. The author shows the effectiveness of the use of computer training and simulation game "Virtual pedagogy" in the development of creative skills, cognitive interests of students.
Keywords: computer training and game business; information technology; education